Experimental and modeling studies of methylene blue adsorption onto particles of peanut shell. (1st November 2016) - Kiliç, Fatih; Sarici-Özdemir, Çiğdem
ABSTRACT: In this study, adsorption of methylene blue from aqueous solution onto peanut shell has been investigated. Experimental data obtained from dye adsorption have been studied by five two-parameter (Langmuir, Freundlich, Dubinin–Radushkevich, Temkin, and Frumkin) and five three-parameter (Redlich–Peterson, Sips, Toth, Radke–Prausnitz, and Koble–Corrigan) isotherm models. Eight nonlinear error functions (sum squares errors, hybrid fractional error function, Marquardt's percent standard deviation, average relative error, sum of absolute error, the coefficient of determination, nonlinear chi-square test, and standard deviation of relative errors) were examined for isotherm equations. In order to explain the adsorption kinetics fit of pseudo-first-order, pseudo-second-order, Elovich, and intraparticle kinetic models were used. The best fitting isotherm model was the Radke–Prausnitz and kinetics model was pseudo-second-order. Adsorption experiment showed that the maximum capacity of agricultural waste for methylene blue was 67.57 L · g −1 at 25°C.